Long-term changes of temperature and humidity regime on Kamchatka Peninsula - Olga A. Shkaberda; Lubov N. Vasilevskaya (Известия ТИНРО, 2014)
Changes of temperature and humidity regime in Kamchatka are estimated on the seasonally and annually averaged data of long-term (1951-2009) monitoring on air temperature and precipitation at 10 meteorological stations (2-months natural synoptic seasons are used for averaging, as pre-winter, early winter, late winter, spring, summer, and autumn). Epochs with extremely dry and humid seasons are detected for certain climatic sub-regions of Kamchatka taking into account both temperature and precipitation anomalies (Pedya index - S). Besides, long-term changes of the sea surface temperature in the coastal areas of the Okhotsk and Bering Seas are determined that reflect thermal interaction between the atmosphere and ocean. The warming trend is revealed for the whole investigated region that is the most expressed in the pre-winter and late winter seasons and the less pronounced in the south and north of the Peninsula (slight cooling is observed in its northern and northeastern areas in early winter). The sea surface has a tendency to warm, too, but slower than the air; the greatest warming trend is observed in the coastal Okhotsk Sea in spring and autumn and in the coastal Bering Sea in autumn. Annual precipitation has opposite changes in different parts of the Peninsula: its volume tends to decrease in the north and the south, on the western and northeastern coasts, and in the Kamchatka River valley but tends to increase in the central mountainous area and on the eastern coast.